Pengembangan Usaha Kerajinan Takraw Anyaman Rotan Melalui Teknologi Pemasaran Media Sosial Di Desa Kalebarembeng Kecamatan Bontonompo Kabupaten Gowa - Aminuddin (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The takraw ball craft business is located in the Bontomanai hamlet, Kalebarembeng Village, Bontonompo District, Gowa Regency. The main income of the community apart from the takraw ball woven craft is mostly farmers and traders. The aim of the Community Empowerment Program activities is to improve the standard of living of the community by developing partner businesses and improving marketing technology for the woven rattan takraw ball craft business in Kalebarembeng Village, Bontonompo District, Gowa Regency by providing business development training and marketing technology training for the rattan woven takraw ball craft business. To achieve this goal, two approaches were taken. Firstly, to increase knowledge in developing the rattan woven takraw ball craft business and secondly to increase technological capabilities and skills in marketing the rattan woven takraw ball craft business so that the problems faced by the partners can be resolved well.